Structural and molecular analysis of the cancer prostate cell line PC3: Oocyte zona pellucida glycoproteins - Costa, Jéssica; Pereira, Rute; Oliveira, Jorge; Alves, Ângela; Marques-Magalhães, Ângela; Frutuoso, Amaro; Leal, Carla; Barros, Nuno; Fernandes, Rui; Queiroz Almeida, Diogo; Barreiro, Márcia; Barros, Alberto; et al. (Tissue & cell, 2018)
•PC3 cell line demonstrates two types of grow, adherent and in suspension.•Cells from each type of growing pattern present different ultrastructure.•Zona pellucida proteins expression was found on both prostate cancer and PC3 cells.•Pavement-cells (adherent) have a higher expression of ZP1, ZP3 and ZP4 mRNA.•A greater expression of ZP3 was found on both types of PC3 cells. The human oocyte zona pellucida (ZP) is made of four glycoproteins, ZP1-ZP4. Recently, the prostate adenocarcinoma and prostate cancer PC3 cell-line were shown to express the human oocyte ZP3 glycoprotein, which was evaluated in a single report subject to patent. To further clarify whether oocyte zona pellucida glycoproteins are expressed in prostate cancer tissue and PC3-cells, in this report we evaluated protein expression of the four ZP glycoproteins in normal prostate tissue, prostate adenocarcinoma tissue and PC3-cells, and performed quantitative mRNA expression of the four ZP glycoproteins in the PC3 cell-line. Furthermore, as PC3-cells have not yet been studied in detail regarding their ultrastructural characteristics, in the present report we bring forward the detailed ultrastructure of PC3-cells. PC3-cells were divided into pavement and aggregated cells. We observed new ultrastructural features in pavement and aggregated cells, with the later exhibiting two different cell types. In prostate carcinoma tissue and PC3-cells we found protein expression of the four oocyte glycoproteins, ZP1, ZP2, ZP3 and ZP4. In addition, mRNA expression studies revealed expression of ZP1, ZP3 and ZP4 glycoproteins, but not of ZP2. Interestingly, the ZP1 mRNA product exhibited intron retention.